A Faith-Based Framework for Mitigating Corruption in Nigeria: An Islamo-Christian Perspectives - Abdullahi, Nazifi Dahiru; Bolatito, Ai-Obe Shamsuddin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
This paper investigates coeruption using Islamo-christain perspectives. It seeks to answer questions like; why the previous anticorruption efforts failed? What causes the failure? And how a lasting solution to the menace can be achieved? The study employed qualitative research methodology and collected data from Islam and christian scriptures, opinions of practicing Muslims and Christians through interviews, articles from academic database and cases of corruption in Nigeria. The data was analysed thematically. It is discovered that negligence of religious injunctions by Muslims and Christian contributed significantly to moral deterioration in Nigeria which consequently led to the corrupt Nigeria.